2004
DOI: 10.1074/jbc.m312269200
|View full text |Cite
|
Sign up to set email alerts
|

GLUT4 Overexpression or Deficiency in Adipocytes of Transgenic Mice Alters the Composition of GLUT4 Vesicles and the Subcellular Localization of GLUT4 and Insulin-responsive Aminopeptidase

Abstract: The majority of GLUT4 is sequestered in unique intracellular vesicles in the absence of insulin. Upon insulin stimulation GLUT4 vesicles translocate to, and fuse with, the plasma membrane. To determine the effect of GLUT4 content on the distribution and subcellular trafficking of GLUT4 and other vesicle proteins, adipocytes of adipose-specific, GLUT4-deficient (aP2-GLUT4؊/؊) mice and adipose-specific, GLUT4-overexpressing (aP2-GLUT4-Tg) mice were studied. GLUT4 amount was reduced by 80 -95% in aP2-GLUT4؊/؊ adi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
38
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(43 citation statements)
references
References 52 publications
5
38
0
Order By: Relevance
“…striated muscle and adipose tissue (Keller et al, 2002). In addition, the genetic ablation of GLUT4 altered the subcellular distribution and expression levels of the IRAP protein (Abel et al, 2004;Carvalho et al, 2004). These data suggest a functional relationship between IRAP and GLUT4; however, a molecular mechanism has not been elucidated.…”
Section: Introductionmentioning
confidence: 74%
“…striated muscle and adipose tissue (Keller et al, 2002). In addition, the genetic ablation of GLUT4 altered the subcellular distribution and expression levels of the IRAP protein (Abel et al, 2004;Carvalho et al, 2004). These data suggest a functional relationship between IRAP and GLUT4; however, a molecular mechanism has not been elucidated.…”
Section: Introductionmentioning
confidence: 74%
“…Although many mutant proteins inhibit insulin-stimulated Glut4 exocytosis in adipocytes, S10A synapsin is one of only a small number of proteins that specifically inhibits basal Glut4 retention. Others include activated signaling molecules (PI3 kinase and Akt) that presumably modify the activity of the retention machinery proteins (Eyster et al, 2005;Frevert et al, 1998) and overexpression of 'cargo' (Glut4 or IRAP), presumably through saturation of the retention mechanism (Carvalho et al, 2004;Waters et al, 1997). Glut4 retention is also inhibited by siRNA-induced knockdown of two proteins, AS160 and Golgin-160 (Eguez et al, 2005;Larance et al, 2005;Williams et al, 2006).…”
Section: Discussionmentioning
confidence: 96%
“…A number of studies have been reported where the GLUT4 gene was manipulated specifically within muscle tissue, and it was shown that GLUT4 expression was critical for whole body glucose homeostasis (3,6,37). In insulin-resistant states such as obesity and type 2 diabetes, GLUT4 expression was shown to be decreased in adipose cells but not in muscles (1).…”
Section: Discussionmentioning
confidence: 99%